Prenatal exposure to bisphenol A disrupts RNA splicing in the prefrontal cortex and promotes behaviors related to autism in offspring - Pawinee Panjabud; Songphon Kanlayaprasit; Surangrat Thongkorn; Kwanjira Songsritaya; Pattanachat Lertpeerapan; Kasidit Kasitipradit; Thanawin Jantheang; Suthathip Sarobol; Thanit Saeliw; Valerie W. Hu; Takeshi Imai; Tewarit Sarachana (Scientific Reports)
Abstract Prenatal exposure to bisphenol A (BPA), a common endocrine disruptor, has been increasingly implicated in neurodevelopmental disorders, including autism spectrum disorder. This study explores the molecular mechanisms by which prenatal BPA exposure affects alternative RNA splicing in the prefrontal cortex and investigates the potential link between alternative RNA splicing and autism-related behaviors in rat offspring. Using RNA sequencing and high-resolution melting real-time PCR, we identified differentially alternative splicing events associated with autism candidate genes. Gene ontology and pathway analyses revealed significant enrichment of differentially alternative splicing genes and neurological pathways relevant to autism. BPA appears to act through autism-related transcription factors, affecting RNA-binding proteins. Altered expressions of these RNA-binding proteins influenced alternative RNA splicing events within key autism-related genes, implicating them in disrupted synaptogenesis. Behavioral analyses of offspring exposed to BPA revealed autism-associated traits, including hyperactivity, anxiety, and aggression, which correlated with the observed sex-specific alternative RNA splicing patterns. These findings suggest that BPA-induced alterations of transcription factors and RNA-binding proteins affect alternative RNA splicing and synaptic development, potentially contributing to autism pathophysiology. This research underscores the role of environmental factors in autism etiology and highlights the importance of awareness and preventive measures against prenatal BPA exposure.